Gust response of a rotating circular cylinder in the vortex suppression regime. (December 2017) - Rana, Khushbakht; Manzoor, S.; Sheikh, N.A.; Ali, Muzaffar; Ali, H.M.
Highlights: Effect of upstream gust is numerically studied on rotating circular cylinder in cross-flow. Intensity of gust influences the 'silent region' of the rotating cylinder for 2 ≤ α ≤ 5. Vortex detachment and variation in Nusselt number is noted in the 'silent region'. Abstract: Numerical investigation is carried out to observe the effect of a single gust impulse on free stream flow and forced convection heat transfer across a two-dimensional steadily rotating circular cylinder. The non-dimensional rotation rate α is varied within the vortex suppression regime i.e. 2 ≤ α ≤ 5 at a Reynolds number of 140 and Prandtl number of 7. Seven different gust profiles in the order of increasing differential kinetic energy imparted to the mean flow; are implemented and their effects are compared. Constant wall temperature (CWT) boundary condition is used to solve the governing equations i.e. continuity, momentum and energy equations. This study notes vortex detachment and asymmetric convection of vortical structures even in the otherwise typical vortex suppression regime of the dimensionless rotation rate due to the inclusion of the gust impulse. Moreover, vortical structure detachment takes place at varying frequencies and only for a very short duration of time. Further evidence pertaining to the average Nusselt number and shear layer stretching and distortion is presented and discussed.